An unproclaimed empire : the Grand Duchy of Lithuania : from the viewpoint of comparative historical sociology of empires /: the Grand Duchy of Lithuania : from the viewpoint of comparative historical sociology of empires. (2017) - Norkus, Zenonas
No abstract available